Synthesis of functionalised azepanes and piperidines from bicyclic halogenated aminocyclopropane derivatives. Issue 25 (15th June 2017) - Chen, Cheng; Kattanguru, Pullaiah; Tomashenko, Olesya A.; Karpowicz, Rafał; Siemiaszko, Gabriela; Bhattacharya, Ahanjit; Calasans, Vinícius; Six, Yvan
Abstract : Reductive amination of aldehydes or ketones with suitable dihalogenated bicyclic aminocyclopropanes gives functionalised ring-expanded products in a single step. Abstract : A series of 6, 6-dihalo-2-azabicyclo[3.1.0]hexane and 7, 7-dihalo-2-azabicyclo[4.1.0]heptane compounds were prepared by the reaction of dihalocarbene species with N -Boc-2, 3-dihydro-1 H -pyrroles or -1, 2, 3, 4-tetrahydropyridines. Monochloro substrates were synthesised as well, using a chlorine-to-lithium exchange reaction. The behaviour of several aldehydes and ketones under reductive amination conditions with deprotected halogenated secondary cyclopropylamines was investigated, showing that this transformation typically triggers cyclopropane ring cleavage to give access to interesting nitrogen-containing ring-expanded products.